Association between thymidine kinase 1 and clinicopathological high-risk features in breast cancer - Yanze Liu; Jiaqi Liu (Medicine, 2026)
Thymidine kinase 1 (TK1) is a cell-cycle-regulated enzyme involved in DNA synthesis and is closely linked to tumor cell proliferation. This study investigated whether serum TK1 concentration is associated with clinicopathological high-risk features in breast cancer (BC) and whether TK1 changes after neoadjuvant chemotherapy (NACT). This retrospective single center cohort included 410 patients with invasive BC. Serum TK1 was analyzed according to age, lymph node metastasis (LNM), histological grade, Ki-67, circulating tumor cell (CTC) status, tumor size, and BC subtype. Subtypes were analyzed as Luminal A, Luminal B, and a human epidermal growth factor receptor 2 (HER2)-positive/triple-negative breast cancer (TNBC) high-risk group (25 HER2-positive and 35 TNBC cases). Multivariable linear regression included age, LNM, histological grade, Ki-67, CTC status, and subtype. Normality, sensitivity, and nonparametric analyses were performed. In the full-cohort, serum TK1 was higher in patients aged 30%. The univariable difference among the 3 subtype groups was not statistically significant (ANOVA P = .239); however, after adjustment, the HER2-positive/TNBC group had higher serum TK1 than Luminal A tumors ( B = 0.197, 95% CI 0.103–0.291, P < .001). CTC status was not independently associated with TK1 ( B = 0.020, 95% CI −0.081–0.122, P = .693). The full-cohort sensitivity model excluding CTC yielded consistent results. In the NACT subgroup, serum TK1 decreased after treatment overall and in both complete response and partial response subgroups. Serum TK1 was independently associated with younger age, LNM, higher histological grade, Ki-67, and the HER2-positive/TNBC high-risk phenotype. Serum TK1 also decreased after NACT. Because survival, recurrence-free survival, and disease-free survival were not evaluated, these findings support TK1 as a proliferation-related biomarker for risk stratification and treatment response monitoring, but not as definitive evidence of long-term outcome prediction.